2021
DOI: 10.1371/journal.pntd.0009145
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of drug resistance mutations among Mycobacterium bovis lineages in the Americas

Abstract: Identifying the Mycobacterium tuberculosis resistance mutation patterns is of the utmost importance to assure proper patient’s management and devising of control programs aimed to limit spread of disease. Zoonotic Mycobacterium bovis infection still represents a threat to human health, particularly in dairy production regions. Routinary, molecular characterization of M. bovis is performed primarily by spoligotyping and mycobacterial interspersed repetitive units (MIRU) while next generation sequencing (NGS) ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Since the glpK gene encodes an enzyme involved in glycerol metabolism ( Supplementary Figure 1 ), and early studies concluded that the growth of M. tuberculosis was strongly promoted by the addition of glycerol to the medium during in vitro culture, 27 , 28 we monitored the growth curves of different M. bovis glpK HT strains. Similar to M. tuberculosis H37Rv, the growth of M. bovis glpK 7C HT strain was promoted in the glycerol-based medium compared to pyruvate ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the glpK gene encodes an enzyme involved in glycerol metabolism ( Supplementary Figure 1 ), and early studies concluded that the growth of M. tuberculosis was strongly promoted by the addition of glycerol to the medium during in vitro culture, 27 , 28 we monitored the growth curves of different M. bovis glpK HT strains. Similar to M. tuberculosis H37Rv, the growth of M. bovis glpK 7C HT strain was promoted in the glycerol-based medium compared to pyruvate ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“… 34 However, in many countries, first and second line antibiotics against TB are not approved for animal consumption. 28 This further complicates the identification of the sources implicated in the acquisition of mutations conferring resistance to these drugs since multiple factors could participate in this process. Canonical mechanisms of resistance are generally grouped into three broad categories: target modification, drug inactivation, and drug transport.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is not rare in M. tuberculosis , further studies targeting this mutation in M. bovis might provide more insight into this mechanism of resistance in this species. Similarly, isoniazid (INH) resistance, though less common, has been demonstrated from animal-recovered isolates and is a cause for concern [ 82 , 83 , 84 , 85 ]. INH resistance can be associated with mutations in several genes ( fabG1 , inhA , iniC , kasA , and katG ); here, the five genomes with this predicted mutation involved fabG1 .…”
Section: Discussionmentioning
confidence: 99%
“…INH resistance can be associated with mutations in several genes ( fabG1 , inhA , iniC , kasA , and katG ); here, the five genomes with this predicted mutation involved fabG1 . A previous study identified the katG mutation only among a set of 2074 genomes of M. bovis lineages in the Americas [ 85 ]. Another study previously performed in Catalonia also identified polyresistant M. bovis infection in human and sympatric sheep [ 86 ], highlighting the importance of a One Health approach in TB control to prevent the spread of TB between humans and livestock, considering the drug resistance in strains circulating among livestock.…”
Section: Discussionmentioning
confidence: 99%